The camel (Camelus dromedarius): A bibliographical review - Mukasa-Mugerwa, E. (International Livestock Centre for Africa, 1981)
Describes the origin, distribution, reproductive performance and nutritional characteristics of the camel i.e. Camelus dromedarius, identifying major and minor camel diseases, and assessing the camel's potentials for meat/milk production, transport, ploughing, milling and production of hides and skins. Discusses some socio-economic factors influencing camel herd management and production; w. proposals for future research and a review of literature on the dromedary in Africa and Asia.